1988
DOI: 10.2337/diab.37.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Splanchnic Amino Acid and Glucose Metabolism During Amino Acid Infusion in Dogs

Abstract: With the organ-balance technique, we studied amino acid and glucose metabolism by hepatic and extrahepatic splanchnic tissues in awake dogs in the postabsorptive state and during a 3-h intravenous amino acid infusion. Dogs received a high (1.4 g/kg body wt, n = 5) or low (0.7 g/kg body wt, n = 8) dose of amino acids. In four of the latter dogs, the dose was delivered into a mesenteric vein. During the basal period there was a net removal of gluconeogenic amino acids (particularly alanine), but not branched-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…These results are in line with studies in dogs that have shown that infusion of AA, which were disposed by about 90% into the splanchnic tissues, inducing a rise in hepatic glucose production [44]. Thus, direct effects of AA on GNG are likely explained by increased supply of gluconeogenic substrates.…”
Section: Discussionsupporting
confidence: 80%
“…These results are in line with studies in dogs that have shown that infusion of AA, which were disposed by about 90% into the splanchnic tissues, inducing a rise in hepatic glucose production [44]. Thus, direct effects of AA on GNG are likely explained by increased supply of gluconeogenic substrates.…”
Section: Discussionsupporting
confidence: 80%
“…The concentration of glycine required to provoke the tight binding of folylpolyglutamates to serine hydroxymethyltransferase is 0.1 m M , well below the actual concentration of free glycine in rat liver (5 mM) (24). The concentration of plasma glycine in the human (25,26), dog (27), and rat (24,28), is about 0.2 mM, while that in the pig is higher (1.0 mM) (29) . This suggests that the concentration of glycine in pig liver is at least 1.0 mM.…”
Section: The Major Folate Binding Proteinsmentioning
confidence: 83%
“…Although the above suggests skeletal muscle to be the major site for glutamine synthesis during amino acid infusion, it is not likely to be the predominant contributor. Studies in human adults show that only 25-30% of infused amino acid nitrogen is taken up by the skeletal muscle and 70% is removed by the splanchnic compartment (23,27,28). Thus, it is likely that the observed increase in Ra of glutamine in response to increased amino acid infusion is contributed by both the skeletal muscle as well as by the splanchnic organs.…”
mentioning
confidence: 98%